Empanado de frango com polpa de pequi: desenvolvimento e avaliação sensorial - Godoi, Fernanda Paulla de (2017)
The peki fruit(Caryocar brasiliense Camb.) stands out among the fruits from various Cerrado native frui species.). However, it is still not very popular throughout Brazil, because it has a very characteristic taste and aroma, and is still restricted to preserves, creams and chestnut oil. The objective of this work was to develop breaded chicken patties with peki fruit pulp and to evaluate the effect of different concentrations of peki fruit pulp and of different cooking methods on acceptance and purchase intention. For the preparation of the breaded ckichen patties, chicken breast, ice water, salt, erythorbate, sodium phosphate, garlic, parsley, pepper, onion, curing salt and peki fruit pulp were used in the following concentrations (2.5, 5.0, 7.5 and 10.0%). At coverage stage, corn starch, water, and onion and garliflavored breadcrumbs were used. The breaded chicken patties were prepared to consume using four different cooking methods (air-fryer, microwave, conventional oven and fried by oil immersion) andevaluated for acceptance tests and purchase intent. The texture, flavor, color and aroma attributes were evaluated. There was no rejection in any of the samples, in spite of the peki fruit pulp concentration, but the degree of acceptance varied from one cooking method to another. The cooking method most accepted by consumers were in electric airfryer and conventional oven.